Advancing the Process Control Level of Key Processes within the Integrated Logistics Centre of Rolls-Royce plc. in Derby as Part of the “Improvement Journey to Process Excellence” - Brendecke, Peter (2009)
The company Rolls-Royce is engaged in a five year improvement plan that aims for excellent processes company-wide. One element of this plan is the improvement of the process control, which means the reduction of the variation in the process inputs and outputs.